English Learning Fomo: Can Increase Motivation to Learn English as a Second Language (ESL) - Derine Yosando (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
FOMO is commonly defined as the Fear of Missing Out. Humans are social creatures who crave following what's trending, whether on social media or in their immediate environment. FOMO permeates the lives of many people, especially students. At this stage, students typically desire to learn more, especially when learning a foreign language: English. This study aims to determine the extent to which students' learning motivation at all levels, driven by FOMO, is driven by ongoing, essential needs triggered by social pressures in the digital age. Using a questionnaire, this method was designed to measure FOMO levels, learning motivation (intrinsic, extrinsic, and simply due to FOMO), the influence of social media, and English language habits. The results of this study will conclude that students' English learning outcomes are affected by FOMO in their motivation to learn (intrinsic-extrinsic). Educational strategies should focus on developing clear and relevant personal goals, rather than simply following trends. Thus, English learning can become a genuine necessity that has a lasting positive impact on high school students in the digital age.